Da Antonello Petrucci a Vito Pisanello: alcune considerazioni sui primi segretari regi nella Napoli Aragonese (1458-1501) - Alessio Russo (Laboratoire Italien)
This article, through the analysis of the different characters who succeeded in the office, offers a new, although not exhaustive, interpretative framework about the first secretary in the aragonese Kingdom of Naples of the 15th century and the beginning of the 16th century.